(3GdGcJaGA aj eZGRi GdeUWaj Udi Gddg Ydjg hSde heZGRi GdKdGKg GdNdaGAs - (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3BNQgG (B:s
(3jRhQc Yf fSNI GdbQGQ SdjakG ajdbGc Hg HENdGU ced GdcJGH s
(3GdfbU ai Gdajde abW hdcfg ehLhO ai GdeNWhW GdCUdis
(3GfXQ Qbe (B56s
(3hQbe (B584(3JGQjNs
(3fSNI QGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJGQjNs